Go team! : take your team to the next level - Blanchard, Kenneth H. (Berrett-Koehler Publishers, 2007)
Effective teams are increasingly recognized as crucial to business success, but few people really understand how to build a team that taps and blends the skills of each member for a winning whole. In clear, simple language, "Go Team!" shows how to create that powerhouse team. Authored by the bestselling author Ken Blanchard, whose various leadership books have sold over 13 million copies, "Go Team!" outlines a three-step process that can benefit work teams, project teams, problem solving teams, leadership teams, and more. The book begins by defining what constitutes a great team, using example